STATE SUPPORT FOR DEVELOPMENT OF PERSONNEL POTENTIAL IN HOSPITALITY IN CHINA - Yu Yi (Статистика и экономика, 2016)
The article considers the state support fordevelopment of personnel potential in hospitality business in China. Hospitality frameshave quantitative and qualitative characteristics. The gap between the needs of business organizations of hospitality for highlyqualiﬁed personnel at all levels and theirpresence in such a gigantic scale of countriessuch as China, can only be overcome withthe assistance of the state targeted programplanning. Support for human resourcesdevelopment in the hospitality businessincludes directions - the integration of stateformation, educational institutions and businesses. Further step towards improving thecompetitiveness of Chinese tourism shouldbe to develop a national target program fortraining of hospitality